2010
DOI: 10.1007/s00038-010-0159-y
|View full text |Cite
|
Sign up to set email alerts
|

Possible relationship among socio-economic determinants, knowledge and practices on lymphatic filariasis and implication for disease elimination in India

Abstract: The present analysis highlights the crucial role played by formal education on creating awareness about lymphatic filariasis and how to prevent this vector-borne disease. The importance of education on intervention measures against mosquito breeding and biting is also dealt with in the analysis for planning an effective and sustainable control program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Due to the perception of varied diseases from place to place, it is necessary to conduct an in-depth study of the social, cultural, and economic aspects of the disease before initiating control measures. 25,31,33 This study had shown a wide range of indigenous perspectives from several tribes in Indonesia regarding-lymphatic filariasis, of which only a few had informants could get involved with this research. This may partly be due to limited of time to explore.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the perception of varied diseases from place to place, it is necessary to conduct an in-depth study of the social, cultural, and economic aspects of the disease before initiating control measures. 25,31,33 This study had shown a wide range of indigenous perspectives from several tribes in Indonesia regarding-lymphatic filariasis, of which only a few had informants could get involved with this research. This may partly be due to limited of time to explore.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the success of an MDA program depends upon the target population’s knowledge of the benefits. Knowledge is therefore a vital component in the success or failure of any MDA program [ 11 ]. Poor knowledge leads to poor participation, and poor participation leads to low coverage and persistence in transmission of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge plays an important role in the prevention of LF. Awareness of LF is a suitable method to avoid the disease and remain healthy, as it is known that misunderstanding of illness and health-seeking behavior may improve or interfere with the effectiveness of control measures [ 11 ]. Therefore, we conducted a study of the population living in an LF endemic area in Terengganu state, Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil penelitian menemukan adanya perbedaan akses yang signifikan pada kategori status sosial-ekonomi (Xie et al, 2018). Mereka yang memiliki status sosial-ekonomi lebih baik terbukti lebih bisa memanfaatkan fasilitas pelayanan kesehatan yang ada (Sibley & Weiner, 2011) (Vanamail & Gunasekaran, 2011)(Thin Zaw, Liabsuetrakul, Htay, & McNeil, 2012 (Dhruve, Badgaiyan, & Pandey, 2016) (Yu, Matthes, & Wei, 2018) (Boulton, Carlson, Power, & Wagner, 2018).…”
Section: Pembahasanunclassified